High-current high-stability hydrogen evolution platinum-based catalyst, preparation method thereof and water electrolysis hydrogen production method
The nitrogen-sulphur-co-doped carbon support supported by cobalt nanoparticles was prepared by precipitation and pyrolysis reaction in water, and the platinum nanoparticles were carried out to obtain a platinum-cobalt sulfur-nitrocarbon nanomaterial catalyst, which solved the problem of poor stability of alkaline hydrogen evolution catalysts under large currents in the prior art, and achieved a catalytic effect with high activity and high stability.
Patent Information
- Application Number
- CN202510034728.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-29
AI Technical Summary
It is difficult to prepare alkaline hydrogen evolution catalysts with high catalytic activity and stability under simple and environmentally friendly conditions, especially under large currents, the stability of traditional PtCo catalysts is poor.
By performing a precipitation reaction in water, a cobalt-zinc bimetallic organic framework material is prepared and pyrolyzed under the protection of an inert gas to form a nitrogen-sulphur co-doped carbon support supported by cobalt nanoparticles. Subsequently, a chemical reduction reaction was performed using a platinum salt and a reducing agent, and the platinum nanoparticles were supported to obtain a platinum cobalt sulfur nitrogen carbon nanomaterial (Pt/Co@S-N-C) catalyst.
A catalyst with excellent hydrogen evolution activity and stability under high currents is realized, which simplifies the preparation process, reduces costs, and increases the utilization rate of precious metal platinum.
Smart Images

Figure BDA0005235222540000091 
Figure BDA0005235222540000101 
Figure HDA0005235222550000011
Abstract
Description
Technical Field
[0001] The invention relates to high-value utilization of precious metal platinum, and to a preparation method and application of alkaline electrolyzed water and alkaline anion exchange membrane electrolyzed water. Background Art
[0002] Hydrogen production by electrolysis of water (HER) can achieve efficient production of pure hydrogen due to its pollution-free product, and is a key link in the future development of green hydrogen energy. Platinum group noble metal catalysts, especially Pt / C, are widely used in the field of water electrolysis and fuel cell electrocatalysis. They have good electronic structure and excellent interface adsorption energy, and can effectively catalyze the rapid conversion of reaction intermediates. However, Pt / C is expensive due to the scarcity of noble metals, and its activity is easily reduced due to agglomeration during the reaction. The main method to reduce the price of catalysts is to use non-noble metals to replace platinum group noble metals and improve the atomic utilization efficiency of platinum group noble metals.
[0003] When non-precious metals are used to replace platinum, since their electronic structures are slightly different from those of precious metals, complex interface reaction engineering, heterogeneous structure construction, local environmental regulation or electronic structure regulation are required to improve the catalytic activity and stability of the materials. However, such regulatory methods often have problems such as complex synthesis methods, difficulty in industrialization, high energy consumption or low environmental friendliness. Therefore, how to obtain an alkaline hydrogen evolution catalyst with high catalytic activity and stability that is simple in synthesis and environmentally friendly is a key issue in promoting hydrogen production by water electrolysis and reducing the cost of hydrogen production. Summary of the invention
[0004] The invention aims to provide a high-current and high-stability platinum-based hydrogen evolution catalyst, a preparation method thereof and a method for producing hydrogen by electrolysis of water. The catalyst is a high-current water electrolysis hydrogen evolution catalyst with both high activity and high stability, wherein the active sites are in the form of platinum and cobalt nanoparticles, the sulfur element increases the specific surface area of the base material, and increases the dispersibility of the platinum and cobalt elements, thereby greatly improving the active sites; the obtained platinum-cobalt bimetallic catalyst has excellent hydrogen evolution activity and stability, the preparation method is environmentally friendly, safe and pollution-free, and can effectively improve the utilization rate of the precious metal platinum.
[0005] In a first aspect, the present invention provides a method for preparing a hydrogen evolution platinum-based catalyst, comprising the following steps:
[0006] S1, performing precipitation reaction of dimethylimidazole, a sulfur source, a zinc source and a cobalt source in water to obtain a cobalt-zinc bimetallic organic framework material;
[0007] S2, pyrolyzing the cobalt-zinc bimetallic organic framework material under the protection of an inert gas, so that zinc evaporates and leaves vacancies during carbonization, thereby obtaining a nitrogen-sulfur co-doped carbon support supported by cobalt nanoparticles;
[0008] S3. The nitrogen-sulfur co-doped carbon carrier loaded with the cobalt nanoparticles is subjected to a chemical reduction reaction with a platinum salt under the action of a reducing agent to load platinum nanoparticles on the carrier to obtain the hydrogen evolution platinum-based catalyst.
[0009] Based on the above technical scheme, the hydrogen evolution platinum-based catalyst of the present invention is a platinum-cobalt-sulfur-nitrogen-carbon nanomaterial (Pt / Co@SNC), platinum and cobalt are uniformly loaded on a nitrogen- and sulfur-co-doped carbon substrate, platinum and cobalt in the composite material are both present in the form of single nanoparticles, sulfur increases the specific surface area of the substrate material, and increases the dispersibility of platinum and cobalt elements, thereby greatly improving the catalytic performance of the active sites, and performing excellently under high currents, and sulfur strengthens the anchoring effect on platinum and cobalt, but does not form S-Pt or S-Co bonds, greatly improving the hydrogen evolution stability of the material under high current density. In short, the obtained hydrogen evolution platinum-based catalyst has excellent hydrogen evolution activity and stability, the preparation method is environmentally friendly, safe and pollution-free, and can effectively improve the utilization rate of precious metal platinum.
[0010] In the above-mentioned preparation method of the hydrogen evolution platinum-based catalyst, the sulfur source is at least one of cystamine dihydrochloride, cysteine, thioacetamide, sodium hydrosulfide and methionine.
[0011] In the preparation method of the above hydrogen evolution platinum-based catalyst, the mass of the sulfur source is 11% to 18% of the mass of dimethylimidazole, such as 11%, 12% or 18%. If the sulfur content is too low, carbon nanotubes will not be generated on the catalyst surface.
[0012] In the above-mentioned method for preparing the platinum-based catalyst for hydrogen evolution, the cobalt source is cobalt nitrate hexahydrate;
[0013] Based on the mass of dimethylimidazole, the mass fraction of the cobalt source is 44% to 51% times the mass of dimethylimidazole, such as 44%.
[0014] In the above-mentioned method for preparing the platinum-based catalyst for hydrogen evolution, the zinc source is zinc nitrate hexahydrate;
[0015] Based on the mass of dimethylimidazole, the mass of the zinc source is 65% to 78%, such as 68%, of the mass of dimethylimidazole.
[0016] In the above-mentioned preparation method of the platinum-based catalyst for hydrogen evolution, the precipitation reaction in step S1 is carried out in water. In practice, the inventors compared the catalytic performance of electrocatalysts prepared by precipitation reactions using water and methanol as solvents, respectively. The results showed that the alkaline electrochemical performance of the catalyst prepared using water as solvent was significantly better than that of the catalyst using methanol as solvent. This may be because: when water is used as a solvent, due to its strong polarity and high surface tension, it is conducive to the uniform dispersion of the precursor and the directional growth of the structure.
[0017] In the above-mentioned preparation method of the hydrogen evolution platinum-based catalyst, the precipitation reaction comprises the following steps: adding the aqueous solution of the zinc source dropwise to the aqueous solution of the 2-methylimidazole and the sulfur source, stirring continuously for 4 to 5 hours (such as 4.5 hours), then adding the aqueous solution of the cobalt source, stirring continuously for 4 hours, standing for 20 hours to collect the precipitate; after the precipitation reaction is completed, the method further comprises: drying the precipitate (such as vacuum drying at 60°C) and grinding.
[0018] In the above-mentioned preparation method of the hydrogen evolution platinum-based catalyst, the pyrolysis temperature is 850°C to 900°C, the heating rate is not higher than 5°C / min, and the pyrolysis time is 120 to 150 min. At this pyrolysis temperature, a large number of short carbon nanotubes are produced on the surface of the nitrogen-sulfur co-doped carbon carrier loaded with cobalt nanoparticles, which can greatly increase the specific surface area of the material and is more conducive to the loading of platinum and cobalt nanoparticles. If the pyrolysis temperature is too low, the organic skeleton will not be completely carbonized, the degree of graphitization will be low, and the conductivity will be poor; if the pyrolysis temperature is too high, it will cause the structure to collapse, affecting mass transfer. As an example, take 5°C min -1 The sample was heated to 850°C or 900°C at a rate of 100 °C and kept at this temperature for 2 h.
[0019] In the above-mentioned preparation method of the hydrogen evolution platinum-based catalyst, the platinum salt is selected from any one of chloroplatinic acid, platinum acetylacetonate, potassium chloroplatinite, and platinum chloride, or a combination thereof; preferably, the platinum salt is added in the form of an aqueous solution with a concentration of 20 to 60 mg / mL, and ≤440 μL of an aqueous solution of the platinum salt is added to every 50 mg of the nitrogen-sulfur co-doped carbon carrier loaded with the cobalt nanoparticles. Specifically, 440 μL of an aqueous solution of a platinum salt having a concentration of 60 mg / mL is added to every 50 mg of the nitrogen-sulfur co-doped carbon carrier loaded with the cobalt nanoparticles. More specifically, the nitrogen-sulfur co-doped carbon carrier loaded with the cobalt nanoparticles is added in the form of an aqueous dispersion, such as dispersing every 50 mg of the nitrogen-sulfur co-doped carbon carrier loaded with the cobalt nanoparticles in 35 mL of deionized water.
[0020] In the above-mentioned preparation method of the hydrogen evolution platinum-based catalyst, the reducing agent is selected from any one of ascorbic acid, sodium borohydride, formate, hydrazine or a combination thereof; preferably, the reducing agent is added in the form of an aqueous solution with a concentration not exceeding 0.1 mol / L (such as 0.1 mol / L, 0.05 mol / L), and ≤1.2 mL of the reducing agent aqueous solution is added to every 50 mg of the nitrogen-sulfur co-doped carbon support loaded with the cobalt nanoparticles; specifically, 1.2 mL of an ascorbic acid aqueous solution with a concentration of 0.1 mol / L is added to every 50 mg of the nitrogen-sulfur co-doped carbon support loaded with the cobalt nanoparticles.
[0021] The temperature of the chemical reduction reaction is 60-80° C. and the time is 4-6 hours, such as maintaining at 65° C. for 4 hours.
[0022] In the preparation method of the above-mentioned hydrogen evolution platinum-based catalyst, the chemical reduction reaction comprises the following steps: sequentially adding the aqueous solution of the platinum salt and the aqueous solution of the reducing agent to the aqueous dispersion of the nitrogen-sulfur co-doped carbon support supported by the cobalt nanoparticles to carry out the chemical reduction reaction. After the chemical reduction reaction, the method further comprises: washing the reaction product with water and ethanol three times respectively, collecting the product by centrifugation, and then freeze-drying it under vacuum conditions.
[0023] In the second part, the present invention provides a hydrogen evolution platinum-based catalyst obtained by any of the preparation methods described above.
[0024] In the third part, the present invention provides a method for producing hydrogen by electrolysis of water, comprising the following steps: using the hydrogen evolution platinum-based catalyst as a cathode electrocatalyst to electrolyze hydrogen in an alkaline aqueous solution; or,
[0025] The hydrogen evolution platinum-based catalyst is used as a cathode electrocatalyst to electrolyze water using an alkaline anion exchange membrane to produce hydrogen.
[0026] In the above-mentioned method for producing hydrogen by electrolysis of water, as an example, the alkaline aqueous solution is 1M KOH;
[0027] The electrochemical performance test was carried out by using the nickel foam loaded with the catalyst as the working electrode, the mercury / mercury oxide electrode as the reference electrode, and the graphite rod electrode as the counter electrode.
[0028] The present invention has the following beneficial effects:
[0029] (1) The preparation process of the present invention is simple, requiring only two steps: pyrolysis and wet chemical reduction. The amount of sulfur doping can be precisely controlled by the precursor ratio. The preparation conditions are mild and the cost is low.
[0030] (2) The particle size of the Pt nanoparticles of the present invention is as low as 2.35 nm, the particles are evenly dispersed without agglomeration, and the specific surface area of the carbon substrate is as high as 390.59 m 2 / g;
[0031] (3) The catalyst synthesized by the preparation method of the present invention has excellent alkaline hydrogen evolution performance, and only 16mV is required to reach a current density of 10mA cm-2. At the same time, at a high current density of 500mA cm-2, the overpotential is 268mV, and the stability at high current density is significantly improved, which effectively solves the problem of poor stability of traditional PtCo catalysts under alkaline conditions;
[0032] (4) The catalyst of the present invention is suitable for high current density conditions and has good durability, providing a reliable catalytic material option for large-scale alkaline water electrolysis to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 1 is a scanning electron microscope image of the precursor in specific embodiment 1 of the present invention.
[0034] Figure 2 This is a scanning electron microscope image of the cobalt-sulfur-nitrogen-carbon carrier after pyrolysis in specific embodiment 1 of the present invention, a-2μm, b-200nm.
[0035] Figure 3 It is a transmission electron microscope image of the platinum-cobalt-sulfur-nitrogen-carbon catalyst in specific embodiment 1 of the present invention.
[0036] Figure 4 It is an element scan of the platinum-cobalt-sulfur-nitrogen-carbon catalyst in specific embodiment 1 of the present invention.
[0037] Figure 5 These are the test results of hydrogen evolution performance of the platinum-cobalt-sulfur-nitrogen-carbon catalyst in specific embodiment 1 of the present invention and the comparative example.
[0038] Figure 6 These are the stability test results of the platinum-cobalt-sulfur-nitrogen-carbon catalyst in specific embodiment 1 of the present invention and the comparative example. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.
[0040] The methods used in the following examples, unless otherwise specified, are all conventional methods, carried out according to the techniques or conditions described in the literature in the art or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.
[0041] Example 1
[0042] This embodiment provides a method for preparing a hydrogen evolution platinum-based catalyst (platinum-cobalt bimetallic supported heterogeneous atom-doped carbon catalyst), comprising the following steps:
[0043] (1) 3.94 g of 2-methylimidazole and 0.45 g of cystamine dihydrochloride were weighed and added to 60 mL of deionized water. The mixture was stirred for 1 h until the two solids were completely dissolved to form a clear and transparent ligand A solution.
[0044] (2) Weigh 2.68 g of zinc nitrate hexahydrate into a beaker and dissolve it fully in 30 mL of deionized water under stirring to obtain a transparent solution B. Maintain the solution for 4.5 hours.
[0045] (3) Weigh 1.75 g of cobalt nitrate hexahydrate into a beaker and dissolve it fully in 30 mL of deionized water under stirring to obtain a red transparent solution C.
[0046] (4) Slowly pour solution B into the ligand A solution and continue stirring for 4.5 hours. Thereafter, gradually add solution C. After the addition is completed, continue stirring for 4 hours at room temperature, and then place it in a light-free environment for 20 hours to promote the formation of a purple precipitate. Use a syringe to remove the upper liquid, wash it several times with deionized water, and centrifuge it to obtain a purple precipitate. Finally, dry the product in a vacuum dryer at 60°C, and grind the obtained solid sample with an agate mortar to obtain a pale purple powder sample.
[0047] (5) The samples were transferred into their respective corundum crucibles and covered tightly. These crucibles were then placed in a tube furnace and heated at 5 °C min-1 in an argon atmosphere. -1 The mixture was heated to 850°C at a rate of 1000 °C and kept at this temperature for 2 h. It was naturally cooled at room temperature and the obtained product was ground into black powder using an agate mortar.
[0048] (6) Disperse 50 mg of black powder in 35 mL of deionized water under ultrasonic conditions for 30 min to fully dissolve it, then add 440 μL of chloroplatinic acid aqueous solution (60 mg / mL), add 1.2 mL of ascorbic acid aqueous solution (0.1 mol / L) and ultrasonicate for 5 min before taking it out. Place the mixed solution in a 65 ° C water bath for 4 h. Wash with water and ethanol three times respectively, collect the product by centrifugation, and then freeze-dry under vacuum conditions to obtain Pt / Co@SNC electrocatalyst.
[0049] Figure 1 This is a scanning electron microscope image of the precursor prepared in step (4) of Example 1. The precursor appears as ellipsoidal particles before pyrolysis. Figure 2 This is a scanning electron microscope image of the cobalt-sulfur-nitrogen-carbon carrier obtained after pyrolysis in step (5) of Example 1. After pyrolysis of the precursor, a large number of shorter carbon nanotubes are generated on the surface, which greatly increases the specific surface area of the material and is beneficial to the loading of platinum and cobalt nanoparticles. Figure 3 This is a transmission electron microscope image of the platinum-cobalt-sulfur-nitrogen-carbon catalyst prepared in step (6) of Example 1. Both platinum and cobalt are loaded on the surface of the material in the form of a large number of nanoparticles. The particle size of the Pt nanoparticles is as low as 2.35nm, the particles are evenly dispersed without agglomeration, and the specific surface area of the carbon substrate is as high as 390.59m 2 / g. Figure 4 This is an element scan of the platinum-cobalt-sulfur-nitrogen-carbon catalyst in Example 1. The metal elements and non-metal elements are uniformly loaded, and the metal particles do not agglomerate, indicating that sulfur strengthens the anchoring effect on platinum and cobalt to prevent the particles from agglomerating.
[0050] Example 2
[0051] In this example, a Pt / Co@SNC electrocatalyst was prepared in a similar manner to that in Example 1, except that 0.5 g of cystamine dihydrochloride was added in step (1). The remaining steps were the same as those in Example 1 to obtain a Pt / Co@SNC electrocatalyst.
[0052] Example 3
[0053] In this example, a Pt / Co@SNC electrocatalyst was prepared in a similar manner to that in Example 1, except that 0.7 g of cystamine dihydrochloride was added in step (1). The remaining steps were the same as those in Example 1 to obtain a Pt / Co@SNC electrocatalyst.
[0054] Example 4
[0055] In this example, a Pt / Co@SNC electrocatalyst was prepared in a similar manner to that in Example 1, except that the pyrolysis temperature in step (5) was changed to 900° C. The remaining steps were the same as those in Example 1 to obtain a Pt / Co@SNC electrocatalyst.
[0056] Example 5
[0057] In this example, a Pt / Co@SNC electrocatalyst was prepared in a similar manner to that in Example 1, except that the concentration of the ascorbic acid aqueous solution in step (6) was 0.05 mol / L. The remaining steps were the same as those in Example 1 to obtain a Pt / Co@SNC electrocatalyst.
[0058] Example 6
[0059] In this example, a Pt / Co@SNC electrocatalyst was prepared in a similar manner to that in Example 1, except that the ascorbic acid aqueous solution in step (6) was replaced with a sodium borohydride aqueous solution having a concentration of 0.1 mol / L. The remaining steps were the same as those in Example 1 to obtain a Pt / Co@SNC electrocatalyst.
[0060] Example 7
[0061] In this example, a Pt / Co@SNC electrocatalyst was prepared in a similar manner to that in Example 1, except that the aqueous solution of chloroplatinic acid in step (6) was replaced with an aqueous solution of platinum acetylacetonate having a concentration of 60 mg / mL. The remaining steps were the same as those in Example 1 to obtain a Pt / Co@SNC electrocatalyst.
[0062] Example 8
[0063] In this example, a Pt / Co@SNC electrocatalyst was prepared in a similar manner to that in Example 1, except that the concentration of the chloroplatinic acid aqueous solution in step (6) was 20 mg / mL. The remaining steps were the same as those in Example 1 to obtain a Pt / Co@SNC electrocatalyst.
[0064] Comparative Example 1
[0065] Commercial 20% Pt / C catalyst
[0066] Comparative Example 2
[0067] Same as Example 1, except that cystamine dihydrochloride is not added in step (1), the remaining steps are the same as Example 1, and the specific steps are as follows:
[0068] (1) 3.94 g of 2-methylimidazole was added to 60 mL of deionized water and mixed under stirring for 1 h to form a clear and transparent ligand A solution.
[0069] (2) Weigh 2.68 g of zinc nitrate hexahydrate into a beaker and dissolve it fully in 30 mL of deionized water under stirring to obtain a transparent solution B. Maintain the solution for 4.5 hours.
[0070] (3) Weigh 1.75 g of cobalt nitrate hexahydrate into a beaker and dissolve it fully in 30 mL of deionized water under stirring to obtain a red transparent solution B.
[0071] (4) Slowly pour solution B into the ligand A solution and continue stirring for 4.5 hours. Thereafter, gradually add solution C. After the addition is completed, continue stirring for 4 hours at room temperature, and then place it in a light-free environment for 20 hours to promote the formation of a purple precipitate. Use a syringe to remove the upper liquid, wash it several times with deionized water, and centrifuge it to obtain a purple precipitate. Finally, dry the product in a vacuum dryer at 60°C, and grind the obtained solid sample with an agate mortar to obtain a pale purple powder sample.
[0072] (5) The samples were transferred into their respective corundum crucibles and covered tightly. Subsequently, the crucibles were placed in a tube furnace and heated to 850°C at a rate of 5°C / min in an argon-filled environment and maintained at this temperature for 2 h. After cooling naturally at room temperature, the obtained products were ground into black powder using an agate mortar.
[0073] (6) Disperse 50 mg of black powder in 35 mL of deionized water under ultrasonic conditions for 30 min to fully dissolve it, then add 440 μL of chloroplatinic acid aqueous solution (60 mg / mL), add 1.2 mL of ascorbic acid aqueous solution (0.1 mol / L) and ultrasonicate for 5 min before taking it out. Place the mixed solution in a 65 ° C water bath for 4 h. Wash with water and ethanol three times respectively, collect the product by centrifugation, and then freeze-dry under vacuum conditions to obtain Pt / Co@NC electrocatalyst.
[0074] Comparative Example 3
[0075] The same as Example 1, except that cobalt nitrate hexahydrate is not added in step (1), and the remaining steps are the same as Example 1. The specific steps are as follows:
[0076] (1) 3.94 g of 2-methylimidazole and 0.45 g of cystamine dihydrochloride were weighed and added to 60 mL of deionized water. The mixture was stirred for 1 h until the two solids were completely dissolved to form a clear and transparent ligand A solution.
[0077] (2) Weigh 2.68 g of zinc nitrate hexahydrate into a beaker and dissolve it fully in 30 mL of deionized water under stirring to obtain a transparent solution B. Maintain the solution for 4.5 hours.
[0078] (3) Slowly pour solution B into the ligand A solution and continue stirring for 4.5 hours. Then place it in a lightless environment for 20 hours to promote the formation of purple precipitate. Use a syringe to remove the upper liquid, wash it with deionized water several times, and centrifuge it to obtain a purple precipitate. Finally, dry the product in a vacuum dryer at 60°C, and grind the obtained solid sample with an agate mortar to obtain a lavender powder sample.
[0079] (4) The samples were transferred into their respective corundum crucibles and covered tightly. Subsequently, the crucibles were placed in a tube furnace and heated to 850°C at a rate of 5°C / min in an argon-filled environment and maintained at this temperature for 2 h. After cooling naturally at room temperature, the obtained products were ground into black powder using an agate mortar.
[0080] (6) Disperse 50 mg of black powder in 35 mL of deionized water under ultrasonic conditions for 30 min to fully dissolve it, then add 440 μL of chloroplatinic acid aqueous solution (60 mg / mL), add 1.2 mL of ascorbic acid aqueous solution (0.1 mol / L) and ultrasonicate for 5 min before taking it out. Place the mixed solution in a 65 ° C water bath for 4 h. Wash with water and ethanol three times respectively, collect the product by centrifugation, and then freeze-dry under vacuum conditions to obtain the Pt@SNC electrocatalyst.
[0081] Comparative Example 4
[0082] Same as Example 1, except that in step (1), cobalt nitrate hexahydrate is replaced by ferric acetylacetonate, and the remaining steps are the same as Example 1. The specific steps are as follows:
[0083] (1) 3.94 g of 2-methylimidazole and 0.45 g of cystamine dihydrochloride were weighed and added to 60 mL of deionized water. The mixture was stirred for 1 h until the two solids were completely dissolved to form a clear and transparent ligand A solution.
[0084] (2) Weigh 2.68 g of zinc nitrate hexahydrate into a beaker and dissolve it fully in 30 mL of deionized water under stirring to obtain a transparent solution B. Maintain the solution for 4.5 hours.
[0085] (3) Weigh 2.12 g of ferric acetylacetonate into a beaker and dissolve it fully in 30 mL of deionized water under stirring to obtain a red transparent solution C.
[0086] (4) Slowly pour solution B into the ligand A solution and continue stirring for 4.5 hours. Thereafter, gradually add solution C. After the addition is completed, continue stirring for 4 hours at room temperature, and then place it in a light-free environment for 20 hours to promote the formation of a purple precipitate. Use a syringe to remove the upper liquid, wash it several times with deionized water, and centrifuge it to obtain a purple precipitate. Finally, dry the product in a vacuum dryer at 60°C, and grind the obtained solid sample with an agate mortar to obtain a pale purple powder sample.
[0087] (5) The samples were transferred into their respective corundum crucibles and covered tightly. Subsequently, the crucibles were placed in a tube furnace and heated to 850°C at a rate of 5°C / min in an argon-filled environment and maintained at this temperature for 2 h. After cooling naturally at room temperature, the obtained products were ground into black powder using an agate mortar.
[0088] (6) Disperse 50 mg of black powder in 35 mL of deionized water under ultrasonic conditions for 30 min to fully dissolve it, then add 440 μL of chloroplatinic acid aqueous solution (60 mg / mL), add 1.2 mL of ascorbic acid aqueous solution (0.1 mol / L) and ultrasonicate for 5 min before taking it out. Place the mixed solution in a 65 ° C water bath for 4 h. Wash with water and ethanol three times respectively, collect the product by centrifugation, and then freeze-dry under vacuum conditions to obtain Pt / Fe@SNC electrocatalyst.
[0089] Electrochemical performance test
[0090] Alkaline electrochemical performance test: Weigh 5 mg of the catalyst in the above examples and comparative examples, add 450 μl of isopropanol and 50 μl of 5 wt% Nafion solution, and ultrasonicate under ice water for 1 hour. Take 10 μl of uniform ink and drop it on the 1 cm*1 cm nickel foam washed with hydrochloric acid, acetone and deionized water, and use it as a working electrode after natural air drying. The electrolyte is 1M KOH, the mercury / mercuric oxide electrode is the reference electrode, and the graphite rod electrode is the counter electrode. In the test, cyclic voltammetry (scanning potential of -0.9V to -1.6V, scanning rate of 0.1V / s) is first run for 40 cycles to stabilize the catalyst performance, and then linear voltammetry scanning (scanning potential of -0.9V to -3V, scanning rate of 0.005V / s) is performed. All overpotentials are converted to overpotentials relative to the standard hydrogen electrode, and the conversion formula is E(RHE)=E(Hg / HgO)+0.098+0.0592*pH.
[0091] The alkaline electrochemical test results of each embodiment and comparative example are shown in Table 1.
[0092] Table 1. Electrochemical performance test results (alkaline)
[0093]
[0094] As can be seen from Table 1, the catalyst synthesized in the present invention, especially in Example 1, has excellent alkaline hydrogen evolution performance, and only 16 mV is required to reach a current density of 10 mA cm-2. At the same time, at a high current density of 500 mA cm-2, the overpotential is 268 mV, and the stability is significantly improved at high current density, which effectively solves the problem of poor stability of traditional PtCo catalysts under alkaline conditions.
[0095] Figure 5 The results of the hydrogen evolution performance tests of the specific embodiment 1, comparative example 1 and comparative example 2 of the present invention are shown in Table 1 and Figure 5 From the comparison results of Example 1 and Comparative Example 2, it can be seen that sulfur doping greatly improves the catalytic performance of the catalyst and performs excellently under high current.
[0096] Figure 6 These are the stability test results of the specific embodiment 1 of the present invention and the comparative example 2. Sulfur doping strengthens the anchoring effect on the active metal particles and greatly improves the hydrogen evolution stability of the material at high current density.
[0097] From the comparison results of Example 1 and Comparative Example 3 in Table 1, it can be seen that the alkaline hydrogen evolution performance of the Pt / Co@SNC electrocatalyst with the addition of a cobalt source in Example 1 is significantly better than that of the Pt@SNC electrocatalyst without the addition of a cobalt source. This is because the lack of Co affects the formation and stability of the organic skeleton and loses the electronic interaction between Pt and Co.
[0098] From the comparison results of Example 1 and Comparative Example 4 in Table 1, it can be seen that the alkaline hydrogen evolution performance of the Pt / Co@SNC electrocatalyst with the addition of a cobalt source in Example 1 is significantly better than that of the Pt / Fe@SNC electrocatalyst with the addition of an iron source, which further demonstrates that Co can better regulate the electron density on the Pt surface and exert the synergistic effect of Pt and Co.
[0099] Acid electrochemical performance test: Weigh 5 mg of the catalyst in the above examples 1, 3 and comparative examples 1-2, add 450 microliters of isopropanol and 50 microliters of 5wt% Nafion solution, and ultrasonicate under ice water for 1 hour. Take 10 microliters of uniform ink and drop it on a glassy carbon electrode with a diameter of 3 mm after washing with hydrochloric acid, acetone and deionized water, and use it as a working electrode after natural air drying. The electrolyte is 0.5MH2SO4, the calomel electrode is the reference electrode, and the graphite rod electrode is the counter electrode. In the test, cyclic voltammetry (scanning potential is -0.9V to -1.6V, and the scan rate is 0.1V / s) is first run for 40 circles to stabilize the catalyst performance, and then linear voltammetry scanning (scanning potential is -0.9V to -3V, and the scan rate is 0.005V / s) is performed. All overpotentials were converted to overpotentials relative to the standard hydrogen electrode using the conversion formula E(RHE)=E(Hg / HgO)+0.2828+0.0592*pH.
[0100] The experimental results are shown in Table 2.
[0101] Table 2. Electrochemical performance test results (acidic)
[0102]
[0103] From the comparison results of Example 1 in Table 1 and Table 2, it can be seen that the alkaline hydrogen evolution performance of the Pt / Co@SNC electrocatalyst in Example 1 is improved better than its acidic hydrogen evolution performance. On the contrary, the acidic hydrogen evolution performance of the Pt / Co@NC electrocatalyst not doped with sulfur in Comparative Example 2 is better than the alkaline hydrogen evolution performance. As can be seen from Table 2, sulfur doping does not improve the acidic hydrogen evolution activity. The Pt / Co@SNC electrocatalyst synthesized by the preparation method of the present invention has excellent alkaline hydrogen evolution performance, is suitable for high current density conditions, has good durability, and provides a reliable catalytic material selection for large-scale alkaline water electrolysis hydrogen production, and can be used as a cathode electrocatalyst in alkaline water electrolysis and alkaline anion exchange membrane water electrolysis.
[0104] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, can implement the present invention in a wider range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principle of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departing from the disclosed scope in the application and the changes made with conventional techniques known in the art.
Claims
1. A method for preparing a hydrogen evolution platinum-based catalyst, characterized in that: The steps include: S1, performing precipitation reaction of dimethylimidazole, a sulfur source, a zinc source and a cobalt source in water to obtain a cobalt-zinc bimetallic organic framework material; S2, pyrolyzing the cobalt-zinc bimetallic organic framework material under the protection of an inert gas, so that zinc evaporates and leaves vacancies during carbonization, thereby obtaining a nitrogen-sulfur co-doped carbon support supported by cobalt nanoparticles; S3. The nitrogen-sulfur co-doped carbon carrier loaded with the cobalt nanoparticles is subjected to a chemical reduction reaction with a platinum salt under the action of a reducing agent to load platinum nanoparticles on the carrier to obtain the hydrogen evolution platinum-based catalyst.
2. The method for preparing a hydrogen evolution platinum-based catalyst according to claim 1, wherein: The sulfur source is at least one of cystamine dihydrochloride, cysteine, thioacetamide, sodium hydrosulfide and methionine.
3. The method for preparing a hydrogen evolution platinum-based catalyst according to any one of claims 1 to 2, characterized in that: Based on the mass of dimethylimidazole, the mass of the sulfur source is 11% to 18% of the mass of dimethylimidazole.
4. The method for preparing a hydrogen evolution platinum-based catalyst according to any one of claims 1 to 3, characterized in that: The cobalt source is cobalt nitrate hexahydrate; Based on the mass of dimethylimidazole, the mass of the cobalt source is 44% to 51% of the mass of dimethylimidazole.
5. The method for preparing a hydrogen evolution platinum-based catalyst according to any one of claims 1 to 4, characterized in that: The zinc source is zinc nitrate hexahydrate; Based on the mass of dimethylimidazole, the mass of the zinc source is 65% to 78% of the mass of dimethylimidazole.
6. The method for preparing a hydrogen evolution platinum-based catalyst according to any one of claims 1 to 5, characterized in that: The pyrolysis temperature is 850° C. to 900° C., the heating rate is not higher than 5° C. / min, and the pyrolysis time is 120 min to 150 min.
7. The method for preparing a hydrogen evolution platinum-based catalyst according to any one of claims 1 to 6, characterized in that: The platinum salt is selected from any one of chloroplatinic acid, platinum acetylacetonate, potassium chloroplatinite, and platinum chloride, or a combination thereof; preferably, the platinum salt is added in the form of an aqueous solution with a concentration of 20 to 60 mg / mL, and ≤440 μL of the aqueous solution of the platinum salt is added to every 50 mg of the nitrogen-sulfur co-doped carbon carrier loaded with the cobalt nanoparticles.
8. The method for preparing a hydrogen evolution platinum-based catalyst according to any one of claims 1 to 7, characterized in that: The reducing agent is selected from any one of ascorbic acid, sodium borohydride, formate, hydrazine or a combination thereof; preferably, the reducing agent is added in the form of an aqueous solution with a concentration not exceeding 0.1 mol / L, and ≤1.2 mL of the reducing agent aqueous solution is added to every 50 mg of the nitrogen-sulfur co-doped carbon support loaded with the cobalt nanoparticles; The temperature of the chemical reduction reaction is 60-80° C. and the time is 4-6 hours.
9. The hydrogen evolution platinum-based catalyst obtained by the preparation method according to any one of claims 1 to 8.
10. A method for producing hydrogen by electrolysis of water, characterized in that: The method comprises the following steps: using the hydrogen evolution platinum-based catalyst according to claim 9 as a cathode electrocatalyst to electrolyze hydrogen in an alkaline aqueous solution; or The platinum-based catalyst for hydrogen evolution as claimed in claim 9 is used as a cathode electrocatalyst to produce hydrogen by electrolysis of water using an alkaline anion exchange membrane.
Citation Information
Patent Citations
Platinum-loaded nitrogen phosphorus co-doped carbon material hydrogen evolution catalyst, preparation method and application thereof
CN107623134A
Cobalt monatomic loaded nitrogen-doped carbon oxygen reduction catalyst and preparation method thereof
CN111468167A
Platinum-based catalyst and preparation method and application thereof
CN111841600A
Platinum monatomic hydrogen evolution electrocatalyst and preparation method thereof
CN114134532A
Sulfur coordinated transition metal monatomic catalyst and preparation method thereof
CN116695160A